2022
DOI: 10.3390/vaccines10050757
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy among Healthcare Workers and Trainees in Freetown, Sierra Leone: A Cross-Sectional Study

Abstract: Despite having safe and efficacious vaccines against COVID-19, vaccine hesitancy is widespread. Although a trusted source of information, vaccine hesitancy has been reported among healthcare professionals, yet few studies have explored this phenomenon in sub-Saharan Africa. We conducted a cross-sectional survey of healthcare professionals in Sierra Leone from January to March 2022. Measures included sociodemographic/health-related information and COVID-19-related concerns. From the responses, we constructed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…Similarly, another study in Ethiopia found that older age (>40 years) and being a medical doctor were associated with a lower risk of vaccine-hesitancy. In Nigeria, a study found that HCP who were younger, single and with lower income had more vaccine hesitancy, while being a nurse or doctor was associated with lower hesitancy [17]. In Ghana, being female and having a low income have also been associated with increased COVID-19 vaccine hesitancy [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, another study in Ethiopia found that older age (>40 years) and being a medical doctor were associated with a lower risk of vaccine-hesitancy. In Nigeria, a study found that HCP who were younger, single and with lower income had more vaccine hesitancy, while being a nurse or doctor was associated with lower hesitancy [17]. In Ghana, being female and having a low income have also been associated with increased COVID-19 vaccine hesitancy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Reported rates of vaccine hesitancy have been higher in other studies. A study conducted early in the COVID-19 emergency in Nigeria found higher rates of vaccine hesitancy among HCPs (50%) [17]. In a South African study, 41.0% of HCPs were vaccinehesitant [13] and in Ghana, three out of five HCP were hesitant early in the pandemic (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower scores indicated increased positive attitudes towards vaccines (Martin & Petrie, 2017). For COVID-19 participants, VAX showed acceptable internal consistency (r = 0.70), which was deemed acceptable by Yendewa et al (2022). The reliability of VAX was reported to be 0.84 by Zaidi et al (2021) and >0.90 by Acar-Burkay and Cristian (2022).…”
Section: Vaxmentioning
confidence: 99%
“…The health care experts must first be trained to develop a scientific mind to gather knowledge on virology and novel COVID-19 strains. They often are the influencers in propagating the information, and a recent global survey suggested a greater proportion of health care workers showing their reservations towards vaccination [25] . Seminars must be held to upgrade their knowledge on emerging Delta and Omicron variants and importance of booster doses in relation to these novel strains.…”
Section: Solution; Way Forwardmentioning
confidence: 99%